An Investigation Of Pile Foundations Installed During The Late 19th And Early 20th Century For Re-Use In Building Support - Scott M. Doehla (Deep Foundations Institute, 2008)
A proposed rehabilitation of a 200,000 sf, 75-foot high steel-frame building at the former U.S. Navy Yard in Brooklyn, New York required the review of existing foundation data and an investigation of the foundations with respect to their condition. The building was constructed in stages between 1856 and 1933, including several expansions and interior equipment with isolated foundations. The building has clear spans on the order of 50 feet and at one time supported cranes allowing transport of heavy equipment through the building. The proposed rehabilitation is to include a food manufacturing center and office space having multiple stories. Original construction drawings, available from the Brooklyn Navy Yard Development Corporation?s drawing archive, were reviewed to determine the foundation system supporting the structure. The original drawings provide a window into the methods utilized during late 19th and early 20th century pile foundation construction. The review revealed that the building is supported by pile foundations ranging from timber to concrete-filled steel pipe (depending on the year of construction). Annotations including pile driving records were available on some drawings indicating the design and as-built capacity (using the ENR formula for driving resistance). An investigation consisting of test borings was performed to identify the subsurface conditions underlying the building for evaluating theoretical capacity of the piles. A test pit investigation was performed against existing columns within the structure to expose the piles and pile caps for inspection pertaining to pile condition. The test pit investigation revealed methods utilized during original construction to integrate new columns with existing floor slabs, the use of below-grade brick arches to support a floor slab, and the condition of timber piles which were likely installed up to 120 years ago. The observations made within the test pits were compared with original drawings to evaluate the accuracy of these drawings.